Effects of staining and bleaching on a nanohybrid composite with or without surface sealant - Halacoglu, Derya Merve; Yamanel, Kıvanc; Basaran, Saffet; Tuncer, Duygu; Celik, Cigdem (European Journal of Dentistry, 2016)
Objective: The effect of different staining solutions and a bleaching procedure on color stability and surface roughness of a nanohybrid resin composite were evaluated with or without liquid resin polishing (RP). Materials and Methods: Ninety-six disc-shaped resin composite specimens (A1 Shade, Z550 Filtek 3M ESPE, St. Paul, MN, USA) were prepared and divided randomly into two groups (n = 48). Liquid RP (BisCover LV, Bisco Inc., Schaumburg, IL, USA) was applied in one group (RP) and not in the other (P). Specimen color and surface roughness were determined using a colorimeter and profilometer, respectively. After baseline measurements, each group was divided into four subgroups (n = 12) for immersion in a control (distilled water) or three different staining solutions (ice tea, red wine, and cola) for 1 week. Color and surface roughness were then reevaluated. After measurements, all specimens were bleached using a 35% hydrogen peroxide gel. The color and surface roughness of the specimens were reevaluated. Statistical Analysis: Data were subjected to an analysis of variance for repeated measurements among the groups (P < 0.05). Results: Staining and bleaching did not change the surface roughness of the RP and P groups (P > 0.05). Discoloration in the red wine group was higher than for the other staining solutions for the RP (P < 0.001) and P groups (P = 0.018). Conclusion: Application of liquid RP did not enhance the color stability and surface roughness of the composite resin restoration.
Keywords: Bleaching; nanohybrid composite; staining; surface roughness; surface sealant